The Influence of Workload and Work Environment on Turnover Intention: The Intervening Role of Burnout: (Case Study: Employees of PT Global Yimi Cargo, Bekasi Branch) - Meyyfa Nuri Yanti; Corry Yohana; Christian Wiradendi Wolor (Journal of Management Economics and Financial Accounting, 2026)
This study aims to examine the effects of workload and work environment on turnover intention, with burnout serving as an intervening variable among employees of PT Global Yimi Cargo Bekasi Branch. A quantitative approach with a survey method was employed. The population consisted of 149 employees, selected using the proportionate stratified random sampling technique. Data were collected through questionnaires using a five-point Likert scale and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that workload has a positive and significant effect on burnout and turnover intention, while work environment has a negative and significant effect on burnout and turnover intention. In addition, burnout has a positive and significant effect on turnover intention. Burnout was also found to partially mediate the effects of workload and work environment on turnover intention. The coefficient of determination shows that workload and work environment explain 54.9% of the variance in burnout, while workload, work environment, and burnout explain 48.4% of the variance in turnover intention. These findings support the Job Demands-Resources (JD-R) Theory, suggesting that high job demands and inadequate job resources increase employee burnout, which subsequently leads to higher turnover intention.